Predictive Values of PET/CT in Combination With Regulatory B Cells for Therapeutic Response and Survival in Contemporary Patients With Newly Diagnosed Multiple Myeloma - Cui, Jian; Zou, Zhongqing; Duan, Jiayu; Tang, Wenjiao; Li, Yan; Zhang, Li; Pan, Ling; Niu, Ting (Frontiers in Immunology, 2021)
In multiple myeloma (MM), the whole-body positron-emission tomography/computed tomography (PET/CT) occupies a major position for response assessment and survival prediction, with limitations when representing tumor microenvironment. Regulatory B cells (Bregs) have been reported to have an inhibitory immune function, which contributes to bone marrow- (BM-) immunosuppressive microenvironment for MM. Therefore, we assessed the role of PET/CT in combination with Bregs’ ratios to predict therapeutic response and survival in 120 patients with newly diagnosed MM (NDMM) who were treated with novel agents in our center. Conventional PET/CT parameters including maximum standard uptake value (SUVmax), ratios of BM-derived Bregs within CD19+ B cells and patients’ baseline characteristics were collected to explore their underlying connection after a median follow-up of 24.53 months (range 3.00-42.93 months). SUVmax >4.2 at onset, accounting for 53.2% of NDMM, was confirmed to be associated with both inferior PFS and OS; while the positive correlation between Bregs’ proportions and NDMM patients’ outcomes was explored, with the optimal cutoff ratios of Bregs within B cells as lower than 10%, accounting for 46.2%, to discriminate patients with poorer OS. Accordingly, patients with both SUVmax >4.2 and Bregs’ ratios <10%, accounting for 31.7%, presented lower qualities of both therapeutic response and survival. Collectively, this study may draw attention on the role of combination of PET/CT and Bregs’ ratios when clinical decisions are made for MM in the era of novel agents.